Pengaruh Kepemilikan Institusional, Leverage, dan Pertumbuhan Perusahaan terhadap Nilai Perusahaan dengan Financial Distress sebagai Variabel Intervening - Judapratama, Muhamad; Mappadang, Agoestina (Jurnal Disrupsi Bisnis, 2024)
According to BPS and cnnindonesia.com, Indonesia's economic growth for the initial period of 2020 or quarter 1 was 2.97%, this makes Indonesia's economic growth conditions in 2020 the lowest in the last 20 years. IDX Statistics Report for 2022, the properties & real estate sector in the capital market index is negative and has the lowest ranking, namely -19.11%. This research aims to determine the effect of the GCG variable with a proxy for Institutional ownership, the Leverage variable with a Debt to Equity Ratio proxy, and the Company Growth variable with a sales growth proxy on Company Value with a Tobin's q proxy with Financial Distress as an intervening variable. The total sample for this research is the properties and real estate sector companies listed on the IDX in 2018 - 2022, totaling 40 issuers. The analysis method used is multiple linear regression, classical assumption test, F test, T test, GLM mediation test, using the Jamovi data processing tool. The research results of institutional ownership, DER and Sales Growth influence company value, institutional ownership and DER influence financial distress. Financial Distress is unable to mediate the relationship between Sales Growth and Company Value.